(untitled) (Ameghiniana, 2013)
GRAPTOLITES IN THE LOWER PART OF THE SILURIAN SEQUENCE,SIERRA DE TALACASTO (SAN JUAN). - Two graptolitic faunas which were discovered in the lower levels of the Silurian sequence exposed in the Talacasto region, Precordillera of San Juan are described. The first one is composed of Climacograptus putillus (Hall) and Climacograptus sp., the other fauna is characterized by Climacograptus aff. Cl. medius Tornquist, Climacograptus aff. Cl. hughesi (Nicholson), Climacograptus cf. Cl. scalaris var. scalaris (Hisinger) and Monograptus sp, The age of the fossiliferous strata is Lower Silurian (Llandoverian).